Surface modification by EDM using Co-Cr sintered powder metallurgy electrode - Khan, Ahsan Ali; Mohammed , Baba Ndaliman; Ali, Mohammad Yeakub; Mansor, Mas Hafizah; Idrus, Nurul-Ain (Trans Tech Publications, Switzerland, 2012)
In this investigation, the powder metallurgy (PM) electrode developed from cobalt (Co)and chromium (Cr) powders was used in electrical discharge machining (EDM). This new Co-Cr sintered electrode was used to machine mild steel workpiece with kerosene dielectric fluid. The main objective is to modify its surface characteristics and secure increased surface hardness. The EDM variables of peak current, pulse duration and pulse interval were applied to investigate these surface properties. Scanning electron microscopy (SEM) / energy dispersive X-ray (EDX)spectroscopy analysis confirmed migration of electrode materials (Co and Cr) onto the EDMed surface. Improved hardness was obtained on the mild steel, the highest being 85.3 HRB. Thus, the Co-Cr electrode introduced into the EDM has the capability of modifying the mild steel surface.